ANALISIS KESENJANGAN ANTARA KEBIJAKAN PENDIDIKAN NASIONAL DAN IMPLEMENTASINYA DI SEKOLAH - Endah Widyati; Iif Pratiwi; Hasmitawati; Hendri Budiman; Desinta Rasyani (STKIP Subang, 2026)
This study examines the gap between national education policies and their implementation at the school level. The research employs a library research method with a qualitative-descriptive approach. Data were collected through document analysis of policy documents and relevant scholarly articles, and analyzed using content analysis through data reduction, coding and categorization, comparative analysis between policy provisions (das sollen) and school practices (das sein), and synthesis. The findings indicate that implementation gaps manifest in four major forms: standards–practice gaps, procedures–implementation gaps, targets–outcomes gaps, and resources–needs gaps. The most prominent gap relates to unequal implementation capacity, particularly disparities in resources, infrastructure, teacher distribution, and technology access across regions and schools. In addition, policy complexity that is not consistently matched by adequate assistance and the lack of full alignment between central and local governance contribute to widening implementation gaps. The study recommends differentiated support for low-capacity schools/regions, strengthening continuous teacher professional development, building an equitable digital ecosystem, and improving data-driven coordination and oversight to enhance policy effectiveness and learning quality.